Pentingnya Pendidikan Akhlak dalam Kehidupan Masyarakat Islam - Mgr Sinomba Rambe; Waharjani Waharjani; Djamaluddin Perawironegoro (Universitas Muhammadiyah Tangerang, 2023)
The importance of maintaining Ukhuwah Islamiah among people who are currently experiencing moral degradation. The phenomenon of lack of mutual respect, indifference between members of society, lack of tolerance, and fading of mutual cooperation are the main problems of Islamic society today. The research entitled